Application of the Principles of al-Tawabi', al-Ashl wa al-Fara' and al-Ashl wa al-Badal in Islamic Family Law - Ah. Soni Irawan; Isniyatin Faizah; Nina Agus Hariati (The Indonesian Journal of Islamic Law and Civil Law, 2025)
The principles of al-tawābi’, al-aṣhl wa al-fara’ and al-aṣhl wa al-badal in the book al-asybah wa al-nadhair are non-fundamental universal principles that are not limited to partial forms. These principles are closely related to one another, but differ in their main points in context. This study aims to describe and apply the principles of al-tawābi', al-aṣhl wa al-fara', and al-aṣhl wa al-badal and their branches to issues of Islamic family law. This study is normative or library research with a qualitative approach using descriptive analysis methods. The results of the study conclude that the application of the al-tawābi' principle includes the validity of the dowry following the validity of the marriage contract, the rights of children such as lineage, inheritance, and maintenance from their father following the validity of their parents' marriage, and the prohibition of marrying the wife's relatives such as brothers, mothers, daughters, aunts, and grandmothers. Meanwhile, the application of the principle of al-aṣhl wa al-fara’ is that the validity of the marriage guardian determines the validity of the marriage contract, murder and non-Muslims become obstacles for heirs to obtain inheritance, and the existence/absence of rights and obligations attached to husband and wife is determined by the status of the marriage bond. The application of the principle of al-aṣhl wa al-badal is that a wife's request for divorce from her husband through khulu' must be replaced with the payment of 'iwadh (ransom/compensation), the guardian judge becomes a substitute for the absence/excuse of the blood guardian in the marriage contract, and the person entitled to bear the responsibility of providing for the family if the husband is unable to provide for his children and wife due to serious illness, then the responsibility shifts to the husband's family.